THE STRUCTURE OF ANTI-POSITIVIST PHILOSOPHY IN LATIN AMERICA - Weinstein, Michel (HUMANITAS DIGITAL, 2021)
AT THE TURN of the twentieth century there was an initiation of independent philosophical speculation in Latin America which has formed the basis for succeeding developments in Hispano-American thought. Breaking the stranglehold of positivism on the Ibero-American mind, such thinkers as Antonio Caso and José Vasconcelos in Mexico, and Alejandro Korn and Carlos Vaz Ferreira in Argentina and Uruguay, took the suggestions of an emerging European and Anglo-American vitalism and wrought them into a distinctive pattern of thought that stressed the significance of ideals and liberty in human life. Taken together, the philosophers of the Latin American golden age created a specific philosophical mentality that has much to offer contemporary thought and that has been duplicated nowhere else in the history of philosophy.